2004
DOI: 10.3348/kjr.2004.5.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Liver Function with MRI Using Gd-EOB-DTPA

Abstract: ObjectiveGadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (Gd-EOB-DTPA) is a newly developed MR contrast agent. After intravenous injection, Gd-EOB-DTPA is gradually taken up by the hepatocytes and eventually excreted via the biliary pathway without any change to its chemical structure. Because of these characteristics, it can be used as a tracer for quantitative liver function testing. The purpose of this study is to develop a noninvasive method of quantitation of the hepatic function using Gd-EOB-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
118
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 26 publications
1
118
0
Order By: Relevance
“…In a liver with impaired function, the receptors on the hepatocytes surface might not work as well as the normal hepatocytes. Some preliminary research suggested that the enhancement of the liver and hepatic function have some relation each other (6,7,19).The results of this study show that only Child-Pugh classifications and ICG-R15s were significantly correlated with liver enhancement. It is clear that albumin and prothrombin activity did not correlate with liver enhancement because these parameters relate to synthesis.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In a liver with impaired function, the receptors on the hepatocytes surface might not work as well as the normal hepatocytes. Some preliminary research suggested that the enhancement of the liver and hepatic function have some relation each other (6,7,19).The results of this study show that only Child-Pugh classifications and ICG-R15s were significantly correlated with liver enhancement. It is clear that albumin and prothrombin activity did not correlate with liver enhancement because these parameters relate to synthesis.…”
Section: Discussionmentioning
confidence: 52%
“…Getting another perspective on our result, it can be said that Gd-EOB-DTPAenhanced MR imaging may be applied to evaluate hepatic function, especially for ''partial hepatic function,'' which can be used for prehepatectomy evaluation. Indeed, some preliminary studies were carried out using animal models to evaluate liver function (7,21). Our results point to a clear correlation between ICG-R15s and liver enhancement, and this should encourage researchers to use Gd-EOB-DTPA-enhanced MR imaging as a new test of hepatic function.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It has recently been found that Gd-EOB-DTPA-enhanced MRC gives added morphological information to conventional T2-weighted imaging (4). In a study on rabbits, Ryeom et al described a method for measuring the hepatic extraction fraction and reported a significant correlation with the plasma indocyanine green (ICG) retention rate 15 minutes after an intravenous injection of ICG (ICG R15), which is an important clinical test for evaluating liver function (17). The authors discuss the potential of Gd-EOB-DTPA-enhanced liver examinations as "a direct, noninvasive technique for the quantitative evaluation of liver function."…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic hepatocyte-specific contrast-enhanced MRI (DHCE-MRI) has previously been used in animal models for the evaluation of hepatic function in various experimental settings, either using semi-quantitative parameters or using deconvolutional analysis (DA) [22][23][24][25]. In human studies, liver parenchymal enhancement after administration of Gd-EOB-DTPA has been shown to correlate with ICG clearance and with liver cirrhosis as assessed by the CPS [26,27], and subsequent biliary excretion has been shown to be delayed in patients with impaired liver function [28].…”
mentioning
confidence: 99%